Carbon nanotubes and expanded graphite based bulk nanocomposites for de-icing applications. (15th February 2021) - Vertuccio, L.; Foglia, F.; Pantani, R.; Romero-Sánchez, M.D.; Calderón, B.; Guadagno, L.
Abstract: This work deals with the design of bulk nanomaterials able to provide ice protection in different applications ranging from civil to aerospace and automotive engineering. Bulk nanomaterials containing dispersed electrically conductive nanoparticles have been formulated. The heating performed through the Joule effect represents an efficient strategy to rapidly contrast extreme cold and humidity conditions, to reduce environmental pollution and to control rheological properties during the process. The effectiveness of the Joule effect has been evaluated for the same resin, characterized by low values of viscosity, containing incorporated carbon nanotubes and two different grades of expanded graphite. The comparison among the chosen fillers highlights that the nanocomposite containing incorporated the unidimensional filler reaches higher temperatures for lower values of the applied voltage. Graphite nanoplatelets can be advantageously used to reduce the viscosity of the nanomaterials. A higher expansion of the graphite allows for obtaining better performance in the heating efficiency.